Passeio virtual na TV digital: apresentação interativa de lugares remotos utilizando a metodologia de imersão 360º do Google Street View - Silva, Demetrius Lacet Ramalho da (2013)
This document presented the relationship between Digital TV - through their interactivity - and virtual tours, regarding the presentation of remote locations based on the methodology employed in virtual tours of Google Street View. Briefly expounded the evolution of some issues necessary for the proper understanding of the project as: Virtual Tour, Google Street View, Tourism and Digital TV, drawing parallels and points of encounter between these social and cultural phenomena, and present a reflection on using conceptual image at the expense of its use as a visual representation only. This research was presented a possible adaptation to the Digital TV visitation to remote places through 360° panoramic tours. As validation of the hypothesis, an application was developed for Digital TV containing a virtual tour to a museum in the light of the methods used to develop virtual tours to the internet in order to demonstrate their use successfully in this new platform. As a complement, a WEB system was developed able to generate this NCL application, suitable for Digital TV.